Human papillomavirus genotype distribution in head and neck cancer: Informing developing strategies for cancer prevention, diagnosis, treatment and surveillance. (February 2021) - Mashiana, S.S.; Navale, P.; Khandakar, B.; Sobotka, S.; Posner, M.R.; Miles, B.A.; Zhang, W.; Gitman, M.; Bakst, R.L.; Genden, E.M.; Westra, W.H.
Highlights: HPV genotypes are unevenly distributed across different sites of the head and neck. Preventive, diagnostic and therapeutic strategies should be customized accordingly. HPV 18 is associated with aggressive small cell transformation. Abstract: Current clinical practice algorithms for HPV testing make no effort to discern the impact of genotypes for patients with head and neck squamous cell carcinoma (HNSC). Data was collected for all patients with HNSCs that had undergone HPV testing at an academic hospital as part of clinical care (2012–2019). Screening was performed using real-time PCR targeting L1 of low and high-risk HPV types, followed by genotyping of positive cases. Genotype status was correlated with age, site and histologic parameters. Of the 964 patients tested, 68% had HPV-positive cancers. Most arose from the oropharynx (OP) (89%) and sinonasal tract (5%). The most frequent genotype was 16 (84.4%) followed by 35 (5.6%), 33 (4.1%), 18 (2.7%), 45 (1.1%), 69 (0.8%) and others (1.3%). There was an association between genotype (16 vs non-16) and tumor origin (OP vs non-OP) (p < 0.0001). HPV18 was associated with transformation to an aggressive small cell phenotype, but HPV16 was not (22% vs 0%, p < 0.0001). Patients with HPV-non-16 OP carcinomas were older than patients with HPV16 OP carcinomas, but the difference was not significant. HPV genotypes are variable and unevenly distributed across anatomic sites of the head and neck. The association of HPV18 with small cell transformation suggests that variants can track with certain phenotypes in ways that may account for differences in clinical behavior. This study challenges the prevailing assumption of HPV equivalency across all high-risk genotypes in ways that may inform preventive, diagnostic, therapeutic and surveillance strategies.